Determination of Senegenin and Tenuifolin in Mouse Blood by Ultra-High Performance Liquid Chromatography-Tandem Mass Spectrometry and Their Pharmacokinetics - Xiuwei Shen; Xiangyi Dai; Yifan He; Congcong Wen; Qingwei Zhang (International Journal of Analytical Chemistry)
An ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the determination of senegenin and tenuifolin in mouse blood was developed. The pharmacokinetics of senegenin and tenuifolin in mice after intravenous (5 mg/kg) and oral (60 mg/kg) administration were studied, and the absolute bioavailability was calculated. A CORTECS T3 column was used, with a column temperature set at 40°C. The mobile phase was acetonitrile and 0.1% formic acid. Gradient elution was adopted, using a flow rate of 0.4 mL/min and an elution time of 4 min. Quantitative analysis was performed using electrospray ionization (ESI) with multiple reaction monitoring (MRM) in negative ion mode. Institute of Cancer Research (ICR) mice were bled from the tail vein after intravenous or oral administration of senegenin and tenuifolin. A UPLC-MS/MS method was established to determine the blood concentrations of each drug in mice, and the noncompartmental model was used to fit the pharmacokinetic parameters. Senegenin and tenuifolin showed a good linear relationship (r > 0.995) within a concentration range of 5–400 ng/mL in mouse blood. The intraday precision was <12%, the interday precision was <14%, and the accuracy was 87–109%. The recovery was >88%, and the matrix effect was 87–94%. The oral bioavailability of senegenin and tenuifolin in mice was 8.7% and 4.0%, respectively. The established UPLC-MS/MS method is suitable for pharmacokinetic studies of senegenin and tenuifolin in mice.